Description of Student Chemistry Learning Difficulties in Acid Base Material Class XI IPA at SMAN 7 Padang - Maryana Dwi Atika; Latisma Latisma (Universitas Negeri Padang, 2022)
Acid base material is a material that is quiet difficult to understand, because 75,5% of class XI science students at SMAN 7 Padang hae not been able to achieve the learning KKM that has been set. This is an indicator that there are still many student who have learning difficulties. Learning difficulties are inability of students to learn to achieve learning objectives and are characterized by low learning outcomes. This research is a descriptive research that aims to describe the level of learning difficulties of students and the factors that influence it in each indicator learning of acid base matter. The subject of this research is class XI IPA 6 SMAN 7 Padang TA 2021/2022 students who number 38 people. The instruments used are two-tier multiple choice diagnostic tests, questionnaire sheets and interviews. Data processing uses descriptive statistical methods. From the results of this research it was obtained that students have difficulty learning in acid base matter. Students' highest learning difficulties lie in the first indicator of analyzing soluble properties based on acid-base theory according to Arrhenius, Bronsted-Lowry, and Lewis by 77.2% with a high category of learning difficulty levels. Based on the results of questionnaires and interviews with students, the factors that cause students' learning difficulties in acid-base materials are seen from the internal factors of students are due to the student's less effective way of learning, namely not concentrating, not making schedules and carrying them out, not repeating materials, not taking notes and reading, and not doing assignments.